2014
DOI: 10.1177/0194599814541629a244
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Use of Cochlear Implants in Older Adults: Results from a Large Consecutive Case Series

Abstract: INTRODUCTIONHearing loss is prevalent in one in three people over the age of 50, and two-thirds of those older than 70 years. 1 Hearing loss in older adults impairs verbal communication, contributes to social isolation, 2 and has been independently associated with poorer cognitive functioning [3][4][5] and incident dementia. [6][7] While hearing aids improve audibility for most individuals with mild to moderate hearing loss, those who suffer from severe to profound hearing loss generally may acquire greater be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Patient‐related factors such as age at implantation, duration and stability of SNHL, sex, and noise exposure should be considered when selecting appropriate candidates in order to maximize hearing preservation outcomes . Our data suggest that increasing age and longer duration of hearing loss have trends toward negative correlations with hearing preservation and speech perception outcomes, consistent with that seen in traditional cochlear implants . Further investigation is warranted in this population.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Patient‐related factors such as age at implantation, duration and stability of SNHL, sex, and noise exposure should be considered when selecting appropriate candidates in order to maximize hearing preservation outcomes . Our data suggest that increasing age and longer duration of hearing loss have trends toward negative correlations with hearing preservation and speech perception outcomes, consistent with that seen in traditional cochlear implants . Further investigation is warranted in this population.…”
Section: Discussionsupporting
confidence: 61%
“…13,35,36 Our data suggest that increasing age and longer duration of hearing loss have trends toward negative correlations with hearing preservation and speech perception outcomes, consistent with that seen in traditional cochlear implants. 37,38 Further investigation is warranted in this population.…”
Section: Fda Approval Of the Nucleus Hybrid L24 Cochlear Implant (Cocmentioning
confidence: 95%
“…Interestingly, the authors also found an increased risk of nonuse with increasing age of the patient at time of implantation. 22 Our cohort included 2 nonusers, one in each age subgroup, as described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is the short postimplantation observation interval. A recent study 47 reported that at 13.5 years after implantation, 83% of elderly patients who received cochlear implants at age 60 years or older continued to use the implant consistently. In another study, 23 elderly patients with unilateral implants maintained their earlier speech perception ability in noise 10 years or more after receiving an implant.…”
Section: Impact Of Hearing Rehabilitation On Cognitive Functionsmentioning
confidence: 99%